Spiritual and Religious Diversity in Prisons Focusing on How Chaplaincy Assists in Prison Management. - Opata, Josiah N. (Springfield : Charles C Thomas Publisher, LTD, 2001)
The goal of this book is to provide an overview for psychologists, psychiatrists, social workers, clergy, corrections professionals, and volunteers of the role that chaplains play in assisting prison management in the rehabilitation of offenders in addition to their ministerial and administrative responsibilities. Organized into six sections, the first discusses the role chaplains play, the need for prison ministry, fundamental counseling skills, and social theories of crime. Chapter 2 is concerned with crime, delinquency theories, and substance abuse and its treatment and prevention. Chapter.
HALF TITLE: SPIRITUAL AND RELIGIOUS DIVERSITY IN PRISONS; TITLE PAGE: SPIRITUAL AND RELIGIOUS DIVERSITY IN PRISONS; FOREWORD; INTRODUCTION; ACKNOWLEDGMENTS; CONTENTS; Chapter 1: THE NEED FOR PRISON MINISTRY AND BASIC COUNSELING ESSENTIALS; Chapter 2: CRIME AND DELINQUENCY AND OTHER PERSPECTIVES; Chapter 3: PROVIDING A WHOLESOME(HEALING) MINISTRY; Chapter 4: DEALING WITH SUCCESSFUL PARENTING ISSUES; Chapter 5: THE NEED FOR PASTORAL SUPPORT (MINISTER OF RECORD); Chapter 6: DEALING WITH NONTRADITIONAL RELIGIONS IN PRISON; ENDNOTES; INDEX.
Description based on print version record.
Keywords: Criminals; Prison chaplains; Rehabilitation; Religious work with prisoners; United States; Social Science; Prison chaplains -- United States; Religious work with prisoners -- United States; Criminals -- Rehabilitation -- United States; SOCIAL SCIENCE / Penology; Electronic books